FOOD ALLERGY AND BIRCH POLLEN: MOLECULAR MECHANISMS AND IMMUNOTHERAPY POSSIBILITIES - Weronika Duda; Monika Domagała; Izabela Domańska; Emilia Majewska; Aleksandra Sagan; Małgorzata Piśkiewicz; Joanna Wiewióra (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Aim of the Study: During the birch pollen season, cross-reactions between the allergen Bet v 1 and the Mal d 1 allergen from apples can induce pollen-related food allergy (prFA), particularly after apple consumption. The aim of this study is to investigate the molecular mechanisms of this allergy and present effective treatment and prevention methods, which could significantly improve the quality of life for allergy sufferers. Review Methods: The PubMed database was used for the literature review. English search terms included: “allergy,” “apple varieties,” “birch pollinosis,” “allergen-specific immunotherapy,” “birch pollen-associated food allergy syndrome,” and “Mal d 1.” Overview of Current Knowledge: Birch pollen allergy is one of the most common pollen allergies, with the Bet v 1 protein responsible for cross-reactive allergic responses following apple consumption. In apples, the Mal d 1 allergen triggers these reactions, which is particularly significant in Central and Northern Europe. Apples with red flesh are considered hypoallergenic due to their low Mal d 1 content and are a beneficial choice for allergic individuals. Various immunotherapy approaches, including sublingual immunotherapy, are utilized effectively to alleviate symptoms and support allergen tolerance. Conclusion: Pollen-related food allergy associated with birch pollen significantly affects the daily lives of allergy sufferers, especially during the birch pollen season. Advances in molecular mechanism research have allowed the identification of apple varieties with lower allergenic potential, enabling their use in immunotherapy and offering hope for improving patients’ quality of life.